Analysis of the Principle of Transparency with Special Reference to Its Implications for the Procedure of International Investment Arbitration - Dussan Laverde, Santiago (2023)
Given that the inherent feature of confidentiality and the demands for transparenc y coexist in the context of international investment arbitration, this paper focuses on an approach that makes a compromise between these two categories. From the perspective of the principle of transparency in the field of international economic law, and taking into account the nature of international arbitration, especially international investment arbitration, a defendable argument can be made to overlook the need for confidentiality and satisfy the demands for transparency in the investment arbitration procedure, without impairing its efficiency.